Business Law, Foreign Direct Investment, and Economic Growth: A Panel Analysis of European Union Member States - Wim, Charles; Wendy, Stephen (Journal of Business and Economic Options, 2025)
This study examines the relationship between foreign direct investment and economic growth in European countries, as it goes through business law. Utilizing panel data from twenty-eight European Union member states, spanning the years of 2010 to 2024, the analysis relies on the application of Partial Least Squares Structural Equation Modeling to assess its results by applying them in evaluating the impacts of foreign investments on economic performance both directly and indirectly. The results suggest that foreign direct investment has an impact on economic growth, which is positive; however, the size of this impact is highly contingent on the strength and quality of a country's legal system operating in the economically relevant business areas. The results also show that countries with well-developed and transparent business regulations are well-positioned to maximize the economic benefits associated with foreign investment. Effective legal structures not only promote higher flows of foreign capital, but they also provide for a stable and predictable environment within which productive economic activities can be encouraged. In contrast, less effective regulatory systems shape the lower potential benefits that can be reaped from foreign direct investment, which modulates the overall contribution of foreign direct investment to economic development. These outcomes demonstrate the strategic importance of sound business laws in improving the nature of foreign direct investment as a source of growth in the European region. The research highlights the importance of policymakers focusing on law reform to strengthen business governance to ensure investor confidence, which in turn supports achievable, sustainable economic advancement among the countries of ECO.